From Justice to Protection A Proposal for Public Health Bioethics - Kottow, Miguel; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
N/A
1.Justice: Basic concepts and critique -- 2. Global ethics: a conceptual dead-end? -- 3. Socioeconomic disparities and health inequities -- 4. Public health bioethics: a new approach -- 5. Ethics of protection: theoretical fundaments -- 6. Ethics of protection: scope and distinct features -- 7. New public health: a challenge for ethics of protection -- 8. Ethics of protection facing public health issues -- 9. Extending the agenda of protection versus precaution.
Keywords: Medicine; Medical ethics; Medicine & Public Health; Public Health/Gesundheitswesen.; Theory of Medicine/Bioethics.